Chordoma of the Clivus and Acute Myeloid Leukemia: Is There a Connection?. Issue 7 (October 2020) - Larkin, Trisha; Macak, Rachel; Lagmay, Joanne; Horn, Biljana
Abstract : Chordoma is a rare cancer in children and understanding the genesis of this tumor may contribute to treatment approaches. Evidence has proposed VDC/IE (vincristine, doxorubicin, cyclophosphamide/ifosfamide, etoposide) as a treatment option for young patients with chordoma to avoid the long-term effects of radiation therapy. We present a case of acute myeloid leukemia developing during treatment of localized chordoma of the clivus in a 20-month-old male. We propose a genomic relationship that may have contributed to the development of clival chordoma and acute myeloid leukemia without a latency period and advocate for genomic sequencing in children with chordoma before the initiation of systemic therapies.